2016
DOI: 10.1074/jbc.m116.740191
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Expression Regulator 1 (Mxr1p) Is Essential for the Utilization of Amino Acids as the Sole Source of Carbon by the Methylotrophic Yeast, Pichia pastoris

Abstract: Unlike Saccharomyces cerevisiae, the methylotrophic yeast Pichia pastoris can assimilate amino acids as the sole source of carbon and nitrogen. It can grow in media containing yeast extract and peptone (YP), yeast nitrogen base (YNB) ؉ glutamate (YNB ؉ Glu), or YNB ؉ aspartate (YNB ؉ Asp). Methanol expression regulator 1 (Mxr1p), a zinc finger transcription factor, is essential for growth in these media. Mxr1p regulates the expression of several genes involved in the utilization of amino acids as the sole sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Recent studies revealed that some amino acids (e.g. glutamate) can be used by P. pastoris as sole source of carbon and nitrogen [20]. We demonstrate that P. pastoris utilize proline in such way.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent studies revealed that some amino acids (e.g. glutamate) can be used by P. pastoris as sole source of carbon and nitrogen [20]. We demonstrate that P. pastoris utilize proline in such way.…”
Section: Discussionmentioning
confidence: 86%
“…glutamate) as sole source of carbon and nitrogen [20]. To study if proline can be used by P. pastoris in such way, tr2-1-GS115 strain was placed in 10 μl of cell suspensions (10 6 , 10…”
Section: Molecular Methodsmentioning
confidence: 99%
“…phaffii is cultured in minimal medium containing yeast nitrogen base (YNB) or nutrientrich medium containing yeast extract, peptone (YP) supplemented with different sources of carbon such as glucose, glycerol, methanol, ethanol, acetate, glutamate etc. Several transcription factors such as Mxr1p, Rop1p, Trm1p, Nrg1p, Mit1p, Mig1p and Mig2p (19,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) regulate the expression of target genes of specific metabolic pathways of K. phaffii. In addition to conventional sources of carbon such as glucose and glycerol, K. phaffii can utilize amino acids such as glutamate as the sole source of carbon and hence can be cultured in YNB medium containing 2% glutamate (YNB+Glu) or YP medium in which amino acids derived from peptone serve as the source of carbon (38).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conventional sources of carbon such as glucose and glycerol, K. phaffii can utilize amino acids such as glutamate as the sole source of carbon and hence can be cultured in YNB medium containing 2% glutamate (YNB+Glu) or YP medium in which amino acids derived from peptone serve as the source of carbon (38). Mxr1p regulates the expression of several enzymes required for glutamate utilization in cells cultured in YP or YNB+Glu (38). Mxr1p regulates the expression of ACS1 encoding acetyl-CoA synthetase 1 during acetate metabolism (37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation